Bat jamboree - Appelt, Kathi (New York : HarperCollins Publishers, 1996)
At an abandoned outdoor movie theater, fifty-five bats perform in a toe-tapping, wing-flapping revue--and await the grand finale.
Keywords: Bats--Fiction; Motion picture theaters--Fiction; Stories in rhyme